Inhibiting DNA methylation activates cancer testis antigens and expression of the antigen processing and presentation machinery in colon and ovarian cancer cells. - Cornelia Siebenkäs; Katherine B Chiappinelli; Angela A Guzzetta; Anup Sharma; Jana Jeschke; Rajita Vatapalli; Stephen B Baylin; Nita Ahuja (PLoS ONE)
Innovative therapies for solid tumors are urgently needed. Recently, therapies that harness the host immune system to fight cancer cells have successfully treated a subset of patients with solid tumors. These responses have been strong and durable but observed in subsets of patients. Work from our group and others has shown that epigenetic therapy, specifically inhibiting the silencing DNA methylation mark, activates immune signaling in tumor cells and can sensitize to immune therapy in murine models. Here we show that colon and ovarian cancer cell lines exhibit lower expression of transcripts involved in antigen processing and presentation to immune cells compared to normal tissues. In addition, treatment with clinically relevant low doses of DNMT inhibitors (that remove DNA methylation) increases expression of both antigen processing and presentation and Cancer Testis Antigens in these cell lines. We confirm that treatment with DNMT inhibitors upregulates expression of the antigen processing and presentation molecules B2M, CALR, CD58, PSMB8, PSMB9 at the RNA and protein level in a wider range of colon and ovarian cancer cell lines and treatment time points than had been described previously. In addition, we show that DNMTi treatment upregulates many Cancer Testis Antigens common to both colon and ovarian cancer. This increase of both antigens and antigen presentation by epigenetic therapy may be one mechanism to sensitize patients to immune therapies.